IMPACT OF SOCIO - ECONOMIC DEVELOPMENT TOWARDS MICRO INSURANCE POLICY HOLDERS (International Journal of Food and Nutritional Sciences, 2022)
India is the largest country in terms of purchasing power parity and is considered one of the fastest emerging economies in the world. Micro Insurance is one of the insurance schemes which are affordable to the poor and the marginalized people who are not included in the insurance. Though the concept of micro insurance was introduced in the year 2005, it could not achieve and reach the unreached people in the country. But, in the present study various factors like that a financial cover, assets holding in our home, savings money for our income levels, problems faced by policyholders, socio and economic impact level and create wealth and so on significantly support the peoples to preference by micro insurance plans. In this research paper involved micro insurance policyholder socio economic impact of micro insurance plans deals with structured questionnaire for framed. The sample size was 398 respondents then statistical tools used for research paper like percentage analysis, one sample t-test, Chi-Square test and ANOVA which are used to estimate the policyholders’ impact level of micro insurance plans. Insurance sectors are playing a major role not only in providing risk coverage to its clients but also in mobilizing the capital to the economic development of the nation.